Altruism and Relational Incentives in the Workplace - Robert A. J. Dur; Jan Tichem (Institute for the Study of Labor (IZA), 2013)
This paper studies how altruism between managers and employees affects relational incentive contracts. To this end we develop a simple dynamic principal-agent model where both players may have feelings of altruism or spite toward each other. The con- tract may contain two types of incentives for the agent to work hard: a bonus and a threat of dismissal. We find that altruism undermines the credibility of a threat of dis- missal but strengthens the credibility of a bonus. Among others, these two mechanisms imply that higher altruism sometimes leads to higher bonuses, while lower altruism may increase productivity and players utility in equilibrium.
Keywords: D23; J33; M52; M55; 330; altruism; spite; incentives; relational contracts; efficiency wages; subjective performance evaluation; Nash bargaining